2021
DOI: 10.1097/tp.0000000000003931
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the Ex Vivo Lung Perfusion Procedure With Continuous Dialysis in a Pig Model

Abstract: Background. Normothermic ex vivo lung perfusion (EVLP) increases the pool of donor lungs by requalifying marginal lungs refused for transplantation through the recovery of macroscopic and functional properties. However, the cell response and metabolism occurring during EVLP generate a nonphysiological accumulation of electrolytes, metabolites, cytokines, and other cellular byproducts which may have deleterious effects both at the organ and cell levels, with impact on transplantation outcomes. Methods. We ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 36 publications
(61 reference statements)
6
19
0
Order By: Relevance
“…De Wolf et al investigated whether dialysis during EVLP affects lung function and pro-inflammatory gene expression but were unable to show a clear benefit of dialysis. 40 Iskender et al reported that cytokine filtration during EVLP could reduce inflammatory cytokines FIGURE 7. Electron microscopic assessment of lower lobes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De Wolf et al investigated whether dialysis during EVLP affects lung function and pro-inflammatory gene expression but were unable to show a clear benefit of dialysis. 40 Iskender et al reported that cytokine filtration during EVLP could reduce inflammatory cytokines FIGURE 7. Electron microscopic assessment of lower lobes.…”
Section: Discussionmentioning
confidence: 99%
“…De Wolf et al investigated whether dialysis during EVLP affects lung function and pro-inflammatory gene expression but were unable to show a clear benefit of dialysis. 40 Iskender et al reported that cytokine filtration during EVLP could reduce inflammatory cytokines and development of pulmonary edema. 41 Our data showed elevations in inflammatory cytokines in EVLP2, which may be partially associated with impaired organ function.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the Toronto protocol, Takahashi et al modified the perfusion method using a syringe infusion pump for continuous delivery of Steen and a multichannel syringe pump for continuous collection of the perfusate, resulting in a significant reduction in IL-6 and IL-8 levels in EVLP perfusate. 115 Nevertheless, because of a greater demand for Steen, this modified perfusion method is of operational complexity and high cost. Wei et al demonstrated the safety and feasibility of installing a dialyzer in the EVLP circuit of porcine lungs instead of frequently exchanging the perfusate.…”
Section: Lack Of a Clearance Mechanismmentioning
confidence: 99%
“…The lung harvest from donor pigs (n = 10) was performed in the Animal Surgery and Medical Imaging Platform (CIMA-MIMA2-BREED-INRAE, Jouy en Josas, France). Heart-lung monobloc harvests were performed using a non-heart-beating donor swine model 33 . Anesthesia was induced by a combination of 1 mg/kg Rompun® 2% (Elanco, Heinz-Lohmann-Strasse 4, Cuxhaven,Germany) and 15 mg/kg Imalgene® 1000 (Boehringer Ingelheim Animal Health, Lyon, France) and pursued with 6% iso uorane.…”
Section: Donor Lung Harvest and Lung Cannulationmentioning
confidence: 99%